Pengaruh Modal Sendiri Dan Kredit Usaha Rakyat (KUR) Terhadap Pendapatan Usaha (Studi Pada UMKM di Desa Padang Birik-Birik Kecamatan Pariaman Utara Kota Pariaman ) - Yasnida; Kartini; Chairani Putri (CV. ITTC INDONESIA, 2024)
This study aims to determine the effect of own capital and people’s business credit (KUR) on business income of MSMEs in Padang Birik-Birik Village, North Pariaman District, Pariaman City. The Population in this study were all MSMEs in Padang Birik-Birik Village in 2021 which amounted to 112 units while the sample was 60 respondent who used their own capital and KUR using the slovin formula with random sampling technique. The data analysis method used statistical test, validity and reliability, classical assumptions, multiple linear regression analysis, hypothesis testing (t test, F test) and the coefficient of determination test. The result showed that the variable of own capital on operating income with a value of tcount = 0,419 and ttable = 1,673 at a significant level of 0,677 > 0,05, so it can be concluded that the variable of own capital has no partial effect on operating income, so it can be concluded that H0 is accepted and H1 is rejected. The result showed that the variable of people’s business credit (KUR) on business income with a value of tcount = 4,959 and ttable = 1,673 at a significant level of 0,00 < 0,05. So it can be concluded that the second hypothesis is accepted. The result of this study indicate that equity and people’s business credit (KUR) simultaneously on business income, obtained a calculated value of Fcount = 46,830 and Ftable = 3,16 with sig = 0,00 < 0,05. The result of calculations using the SPSS 16.0 program can be seen that the coefficient of determination adjusted R square = 0,608. This means that 60,8% of operating income can be explained by the variables of own capital and people’s business credit (KUR) while the remaining 30,2% of the value of operating income is influenced by other variables not examined not in this study.